Shading and its reflections on growth and gas exchanges of Microdesmia rigida (Benth.) Sothers & Prance (Research, Society and Development, 2020)
The objective of this research was to evaluate the effect of shading on growth and gas exchange of seedlings of Microdesmia rigida, keeping them under the levels of 0% (full sun), 50% and 70% shading, arranged in a completely randomized design (DIC), with four replications. Plant height, stem diameter, height/diameter ratio, absolute growth rate, leaf area, plant dry matter weight, dry root/shoot weight ratio, Dickson Quality Index (DQI), transpiration, stomatal conductance, photosynthesis rate, internal CO2 concentration, chlorophyll contents a, b and total were analysed. There was a reduction in the rate of transpiration and increase in stomatal conductance, photosynthesis rate and internal CO2 concentration with increased shading. Shading decreased the concentration of chlorophyll a while promoting an increase in chlorophyll b and total chlorophyll, with no significant difference between the levels of 50% and 70% of shading. The shaded environments provided greater growth in height, diameter, leaf area, in addition to providing greater accumulation of dry mass and IQD. It is recommended to produce seedlings of M. rigida seedlings, during the nursery phase, under 50% shading, as this condition provides the achievement of better seedling quality indexes.